Masjid Jami Al-Ikhlas Sebagai Pusat Penyebaran Dan Pembinaan Islam (Studi pada Kelurahan Mandomai Kabupaten Kapuas Provinsi Kalimantan Tengah) - sury anthy; Siti Aulia (LP2M IAIN Palangka Raya, 2019)
The functionalization of places of worship in this case of mosques for Muslims has been experiencing a lot of development both in terms of architecture and its function for Muslim communities. One of them is the mosque in the Kapuas district of Central Kalimantan province. This study aims to describe how the process of Islamization and the role of the Jami Al-Ikhlas Mosque as a center for spreading Islam and character building of Islam in Kapuas Regency. The research method uses a descriptive qualitative field research. To collect data, the study uses observation, interviews and documentation. The findings of this study indicate that the process of islamization through marriage, Sufism and martial arts. In addition, the mosque also functions as the Islamic teaching place, the recitation of adult, learning to recite Al-Qur’an for children and habsy activities.